ENSURING INFORMATION SECURITY WITHIN THE BANK MANAGEMENT SYSTEM: KEY STRATEGIC APPROACHES (American Journal of Business Management, Economics and Banking, 2025)
The rapid digital transformation of the banking system of the Republic of Uzbekistan, conditioned by the systemic introduction of innovative information and communication technologies and supported by state strategies, has created a secure, efficient, and modern national payment infrastructure. However, while this kind of transformation increases the efficiency, transparency, and competitiveness of financial operations, it has also given a boost to the demand for relevant advanced information security measures. Ensuring the reliability, integrity, and confidentiality of banking data can be reached only via proactive, multilevel approaches that integrate technological innovations, robust cybersecurity frameworks, and effective management of digital risks, which in turn will let the banking sector provide safe, convenient, and high-quality remote financial services both to domestic and international users.